The Ethics of Unhealthy Food and Beverage Advertising to Children: A Bibliometric Analysis and Future Research Agenda - Parul Gupta; Ritu Srivastava; Shalini Jain; Shailendra P. Jain (American Business Review, 2024)
The widely advertised category of unhealthy food and beverages (F&B) is calorie-dense, nutrient-poor, and associated with long-term harm, particularly for children. Business literature has been largely silent regarding the ethicality of its advertising targeting children and lacks clarity on questions future research needs to address. Based on a bibliometric analysis of 1,851 articles published between 1973 and 2021 containing 70,379 citations, we uncovered five intellectual clusters underlying research on the ethics of unhealthy F&B advertising to children (ATC). Importantly, we propose a concrete roadmap featuring actionable and pertinent unanswered questions to stimulate research in this crucial domain.